Ferroelectric material and ferroelectric memory based on two-dimensional material and heteroatom adsorption
By adsorbing transition metal heteroatoms at the pores of two-dimensional materials and regulating them by using electric field, the shortcomings of ferroelectric materials in miniaturization and low power consumption are solved, and the effects of stable ferroelectric performance, adjustability and low power consumption are achieved.
Patent Information
- Application Number
- CN202411789072.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-25
AI Technical Summary
The existing ferroelectric materials have significant shortcomings in miniaturization, regulation performance, power consumption and stability, and cannot meet the needs of ultra-thin memory and low-power applications.
By adsorbing specific transition metal heteroatoms at the pores of two-dimensional materials, the reversibility of ferroelectric properties is achieved using electric field regulation, thereby achieving stable ferroelectric properties in ultra-thin material layers and reducing power consumption.
The stable ferroelectric effect in ultra-thin materials is achieved, the adjustability and flexibility of ferroelectric properties are improved, the power consumption of the device is reduced, and the durability and environmental protection of the material are enhanced.
Smart Images

Figure CN119698056A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ferroelectric materials, and in particular relates to a ferroelectric material and a ferroelectric memory based on two-dimensional materials and heteroatom adsorption. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the advent of the big data era, electronic devices have an increasing demand for efficient and low-power storage. Traditional memory structures (such as SRAM and DRAM) have bottlenecks of high energy consumption and slow speed, so ferroelectric memory (FeRAM) has become an emerging solution. Ferroelectric memory relies on the spontaneous polarization characteristics of ferroelectric materials, which allows data to be stored for a long time without power. Currently widely used ferroelectric materials include PZT (lead zirconate titanate) and HfZrO2 (hafnium zirconium oxide). PZT is the earliest ferroelectric material to be commercially applied, and HfZrO2, as a new type of ferroelectric material, shows good performance and strong compatibility with CMOS processes, which has promoted the development of ferroelectric memory.
[0004] PZT is the earliest commercialized ferroelectric material, although its remnant polarization (Pr) can be as high as 30-40 μC / cm 2 However, when its thickness is reduced to less than 50 nanometers, the ferroelectric performance is greatly reduced and cannot meet the needs of ultra-thin memory. The switching fatigue problem of PZT material also leads to its limited life (usually within 10 11 Performance decays after cycles). In addition, the lead element in PZT has environmental pollution problems and is difficult to meet modern environmental protection requirements.
[0005] In contrast, although HfZrO2 exhibits good miniaturization performance and compatibility with CMOS processes, its remanent polarization value is only 10-50 μC / cm2 despite maintaining ferroelectricity at low thickness. 2 , the polarization strength is relatively low, and the storage density is limited. In terms of operating voltage and power consumption, although the switching voltage of HfZrO2 is lower than that of PZT, it still needs to reach a field strength of 1 to 1.5 MV / cm, which leads to high energy consumption in memory operation, especially in low-power applications. The switching voltage of HfZrO2 depends on the crystalline structure of the material, and the polycrystalline nature of the material leads to large differences in the performance consistency and durability of the device. In addition, HfZrO2 will fatigue under high-frequency operation, causing the ferroelectric performance to decay with time and number of cycles, limiting the durability of the device. Experiments have shown that HfZrO2 devices will not fail after about 10 11Performance degradation will occur after the first read-write cycle, affecting its long-term stability.
[0006] Al 1-x Sc x Nitride-based materials such as N exhibit excellent ferroelectric properties at high temperatures and are highly compatible with CMOS processes. These materials have high remanent polarization values and high operating temperature stability (up to 1000°C), and can maintain ferroelectricity when the thickness is as low as 10nm, making them have great potential in storage and computing applications in extreme environments. However, the current operating voltage of these materials is relatively high (about 2 to 6MV / cm), which requires further optimization.
[0007] In summary, although existing ferroelectric materials have been widely used in ferroelectric memory applications, they still have significant shortcomings in miniaturization, controllable performance, power consumption and stability. Summary of the invention
[0008] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a ferroelectric material and ferroelectric memory based on two-dimensional materials and heteroatom adsorption. The present invention is based on the interaction between two-dimensional materials and heteroatoms, and by adsorbing specific heteroatoms in the pores of two-dimensional materials, the reversibility of ferroelectric properties is achieved by electric field regulation, so that stable ferroelectric properties can be achieved in ultra-thin material layers, while having low power consumption, high controllability and high stability.
[0009] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0010] In the first aspect, the present invention provides a ferroelectric material based on two-dimensional materials and heteroatom adsorption, including two-dimensional materials and heteroatoms, wherein the two-dimensional material is composed of multiple layers of sheets with a pore structure, the heteroatoms are transition metal atoms, and the heteroatoms are adsorbed on one side of the pores. When an electric field is applied, the heteroatoms pass through the sheets through the pores to achieve positive and negative polarization switching.
[0011] The two-dimensional material as the substrate has high electron mobility and rich pore structure, which provides an ideal physical basis for the adsorption and polarization regulation of heteroatoms. On this substrate material, specific transition metal heteroatoms are adsorbed through chemical bonds. These heteroatoms can stably exist in the pores of graphyne, forming a strong interaction between the heteroatoms and the two-dimensional substrate material, resulting in out-of-plane polarization. All heteroatoms can be adsorbed above the pores of two-dimensional graphyne spontaneously or by pre-applying voltage, at which time they are in a specific polarization state. After the electric field is applied, the heteroatoms overcome the potential barrier and pass from the top of the pore to the bottom of the pore. After the heteroatoms pass through the gap, there is a large potential barrier that prevents them from desorbing, thereby achieving the reversal of the polarization direction. The unique interaction mechanism between the two-dimensional material and the heteroatoms significantly reduces the operating voltage of the ferroelectric memory.
[0012] Preferably, the thickness of the two-dimensional material is 15-100 nm. The two-dimensional material film is formed by stacking a few or more layers of Graphene. The thickness of each layer is negligible, and the film thickness depends on the interlayer spacing and the number of layers. The typical interlayer spacing of Graphene is 0.365 nm.
[0013] Preferably, the transition metal atom includes at least one of a manganese atom, a chromium atom, a nickel atom, a cobalt atom and an iron atom.
[0014] By selecting different types of transition metal heteroatoms, the polarization intensity and the height of the reversal barrier can be effectively controlled. The polarization intensity can be significantly adjusted under small voltage changes, and polarization reversal can be achieved at a lower voltage.
[0015] Preferably, the two-dimensional material includes at least one of graphyne, graphene, doped graphene, silicene, doped silicene and transition metal sulfide.
[0016] The two-dimensional materials used completely avoid the use of harmful elements such as lead, overcoming the environmental pollution problem of PZT materials.
[0017] Preferably, the ratio of the number of heteroatoms to the number of pores in the two-dimensional material is (0-1):1, excluding 0. Further preferably, the ratio of the number of heteroatoms to the number of pores in the two-dimensional material is (0.3-0.7):1.
[0018] In order to allow heteroatoms to pass through the pores of graphyne, it is required that at most one heteroatom can be adsorbed at each pore, that is, single atom adsorption. The ratio of the number of heteroatoms to the number of atoms in the two-dimensional material, taking graphyne as an example, there are honeycomb pores in the graphyne structure, and each pore is surrounded by an average of six C atoms.
[0019] In a second aspect, the present invention provides a method for preparing the ferroelectric material as described in the first aspect, comprising the following steps:
[0020] The two-dimensional material and the soluble salt containing the heteroatom are dispersed in a solvent, stirred and then dried to obtain the ferroelectric material.
[0021] Preferably, the soluble salt comprises at least one of hydrochloride, sulfate, nitrate, acetate and a salt whose acid radical contains the heteroatom.
[0022] Preferably, the stirring time is 0.1 to 24 hours, and the drying includes vacuum drying or freeze drying.
[0023] In a third aspect, the present invention provides a use of the ferroelectric material as described in the first aspect in a ferroelectric memory, a nonvolatile memory or a ferroelectric field effect transistor.
[0024] In a fourth aspect, the present invention provides a ferroelectric memory, comprising the ferroelectric material as described in the first aspect.
[0025] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0026] Achieve stable ferroelectric effect in ultra-thin materials and promote memory miniaturization. The ferroelectric performance of existing ferroelectric materials (such as PZT) significantly decreases when the thickness is reduced to less than 50 nanometers, which limits its application in high-density micro-memory. The present invention achieves a stable ferroelectric effect in ultra-thin materials by adsorbing heteroatoms on two-dimensional materials (such as graphyne) and utilizing the interaction between heteroatoms and two-dimensional materials. It can effectively solve the problem of performance degradation of traditional ferroelectric materials during the miniaturization process, thereby promoting the design and application of high-density, ultra-thin memories.
[0027] Improve the adjustability and flexibility of ferroelectric properties to meet the needs of diverse applications. The ferroelectric properties of traditional ferroelectric materials (such as HfZrO2) are limited by the inherent properties of the material, and its polarization intensity and reversal barrier are difficult to adjust flexibly, which limits its applicability in different application scenarios. The present invention achieves precise adjustment of polarization intensity and reversal barrier by adsorbing different heteroatoms at the pores of two-dimensional materials and regulating them through external forces such as external electric fields or strain. This design greatly improves the adjustability and flexibility of material properties and can better meet the needs of different application scenarios.
[0028] Reduce the power consumption of ferroelectric devices and improve energy efficiency. Although the operating voltage of existing ferroelectric memories (such as HfZrO2 devices) has been reduced, they still require a higher switching voltage, resulting in high power consumption and are not suitable for low-power application scenarios. The present invention designs a ferroelectric mechanism for the interaction between two-dimensional materials and heteroatoms, and uses an external electric field to trigger the polarization reversal of heteroatoms. It can achieve polarization switching at a lower voltage, thereby significantly reducing the power consumption of ferroelectric devices and improving their energy efficiency. It is suitable for low-power memory and computing devices.
[0029] Enhance the durability of ferroelectric materials and extend the life of devices. Existing ferroelectric materials (such as PZT and HfZrO2) will fatigue under high-frequency operation, causing the ferroelectric performance to decay over time and the number of cycles, limiting the durability of the device. The present invention reduces the loss of materials during the polarization switching process through the stable adsorption and polarization reversal mechanism of heteroatoms in the pores of two-dimensional materials, significantly improves the cyclic durability of the material, can effectively extend the service life of the device, and meet the needs of high-frequency read and write operations.
[0030] Lead-free environmentally friendly materials are provided to meet the requirements of green environmental protection. Traditional ferroelectric materials (such as PZT) contain lead elements, which pose environmental pollution and health risks and cannot meet environmental protection requirements. The present invention designs a new ferroelectric material by using lead-free two-dimensional materials (such as graphyne) and heteroatoms. It not only has excellent ferroelectric properties, but also avoids the use of harmful elements such as lead, which is in line with the development trend of green environmental protection and is suitable for a wider range of electronic device applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0032] Figure 1 Schematic diagram of the layer structure of the ferroelectric material Mn / GY in Example 1;
[0033] Figure 2 is the system energy and polarization intensity of the ferroelectric material Mn / GY in Example 1 at different reaction stages;
[0034] Figure 3 Schematic diagram of the phonon spectrum of the ferroelectric material Mn / GY in Example 1 and its structure before and after relaxation. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0036] Example 1
[0037] With the two-dimensional gyne film as the substrate, Mn atoms are adsorbed in the pores of the two-dimensional gyne film. The thickness of the two-dimensional gyne film is 15nm. The ratio of the number of Mn atoms to the number of pores in the two-dimensional gyne is 1:2, that is, the ratio of Mn atoms to the C atoms of the two-dimensional gyne is 1:12, recorded as Mn / GY. The layer structure of Mn / GY is shown in Figure 1 As shown, Mn atoms are initially adsorbed above the pores of the graphyne sheet, and the Mn atoms are moved downward by applying an external electric field.
[0038] In this embodiment, a single-layer structure is used to calculate and characterize the performance of the ferroelectric material. In theory, the ferroelectric performance of the single-layer structure can describe the performance of the ferroelectric material. Figure 2As shown in Table 1, the spontaneous polarization intensity of Mn / GY is 63.78pC / m at Reaction 0. At this time, the system is in the ground state and the system energy is recorded as 0eV, which means that the Mn / GY system has a high spontaneous polarization intensity in the stable state. As the reaction proceeds, Mn atoms gradually diffuse from the most stable adsorption site to the pores of graphyne, the system energy gradually increases, and the system polarization intensity gradually decreases. At Reaction 5, Mn enters the pores of graphyne and is in the same plane as the graphyne atoms. At this time, the polarization intensity drops to zero and the system energy reaches the maximum value (0.275eV). Subsequently, Mn diffuses to the other side of the graphyne film. From Reaction 6, Mn / GY shows a negative polarization intensity, which means that the system enters the polarization reversal stage. After that, Mn atoms gradually move away from the pores of graphyne, the system energy gradually decreases, and the negative polarization intensity gradually increases. At reaction 10, Mn is stably adsorbed to the other side of the graphyne film, and the system reaches a stable state again, at which point the spontaneous polarization reaches -63.79pC / m. In the process of Mn atoms diffusing from one side to the other, they cross an energy barrier of 0.275eV, and the spontaneous polarization of the system reverses from 63.79pC / m to -63.79pC / m. Due to the above characteristics, Mn / GY is not only suitable for ultra-miniaturized ferroelectric memory, but also can maintain stable performance under high temperature or complex environments. The adaptability of Mn / GY enables it to be widely used in low-power electronic devices, the Internet of Things, and high-efficiency computing.
[0039] It should be noted that the polarization intensity in bulk materials refers to the electric dipole polarization per unit volume, while the polarization intensity in two-dimensional materials generally refers to the electric dipole polarization per unit area, so the final dimension differs by one unit of length in the denominator.
[0040] Table 1 Polarization intensity and system energy of Mn / GY at different reaction stages
[0041]
[0042]
[0043] like Figure 3As shown, the phonon spectrum calculated based on the first principles does not show imaginary frequencies, indicating that the graphyne (Mn / GY) structure after the adsorption of Mn atoms is at the energy minimum point and has good dynamic stability. In addition, the Mn / GY system was relaxed for 5ps based on the grand canonical ensemble dynamics at room temperature 300K, and the dynamic step was set to 1fs. It was found that the structure after relaxation did not undergo obvious deformation. More importantly, during the relaxation process, all Mn atoms were stably adsorbed on one side of the GY pore and did not spontaneously reverse to the other side of the pore. This fully demonstrates that the Mn / GY system, as a ferroelectric storage material, is non-volatile at room temperature and exhibits good data retention characteristics, which can ensure its stable operation in atomic-level storage devices.
[0044] Example 2
[0045] Two-dimensional graphene and manganese nitrate were dispersed in water at a ratio of 12:1 between the number of C atoms and the number of Mn atoms. After stirring for 12 hours, the reaction solution was collected, centrifuged, washed, and freeze-dried to obtain the ferroelectric material Mn / GY.
[0046] Example 3
[0047] The ferroelectric memory includes Mn / GY in Example 1, and information storage is achieved by applying a reversal voltage to cause polarization reversal of Mn / GY.
[0048] Example 4
[0049] Using two-dimensional gydne film as substrate, Cr atoms are adsorbed in the pores of the two-dimensional gydne film. The thickness of the two-dimensional gydne film is 15 nm. The ratio of the number of Cr atoms to the number of two-dimensional gydne pores is 1:2. The ferroelectric material is recorded as Cr / GY.
[0050] Two-dimensional graphene and chromium (III) sulfate are dispersed in water at a ratio of 12:1 between the number of C atoms and the number of Cr atoms. After stirring for 12 hours, the reaction solution is collected, centrifuged, washed, and freeze-dried to obtain the ferroelectric material Cr / GY.
[0051] As shown in Table 2, the polarization intensity of Cr / GY reaches 32.74pC / m at Reaction 0, and the system energy is 0eV. At Reaction 5, the polarization intensity drops to zero, and the system energy is 0.747eV. The material then enters the polarization reversal stage, showing negative polarization intensity from Reaction 6, and the negative polarization intensity from Reaction 6 to Reaction 10 gradually increases, and finally reaches -32.78pC / m at Reaction 10. In the process of Cr atoms adsorbing and diffusing from one side to the other side, Cr atoms cross an energy barrier of 0.747eV, and the spontaneous polarization intensity of the system reverses from 32.74pC / m to -32.78pC / m.
[0052] Table 2 Polarization intensity and reversal barrier of Cr / GY at different reaction stages
[0053]
[0054]
[0055] Example 5
[0056] Using two-dimensional gydne film as substrate, V atoms are adsorbed in the pores of the two-dimensional gydne film. The thickness of the two-dimensional gydne film is 15nm. The ratio of the number of V atoms to the number of two-dimensional gydne pores is 1:2. The ferroelectric material is recorded as V / GY.
[0057] Two-dimensional graphene and ammonium metavanadate are dispersed in water at a ratio of 12:1 between the number of C atoms and the number of Cr atoms. After stirring for 12 hours, the reaction solution is collected, centrifuged, washed, and freeze-dried to obtain the ferroelectric material V / GY.
[0058] As shown in Table 3, the polarization intensity of V / GY reaches 67.29pC / m at Reaction 0, and the system energy is 0eV. At Reaction 5, the polarization intensity drops to zero, and the system energy is 1.32eV. The material then enters the polarization reversal stage, showing negative polarization intensity from Reaction 6, and the negative polarization intensity from Reaction 6 to Reaction 10 gradually increases, and finally reaches -67.31pC / m at Reaction 10. In the process of V atoms diffusing from one side to the other side, the V atoms cross an energy barrier of 1.32eV, and the spontaneous polarization intensity of the system reverses from 67.29pC / m to -67.31pC / m.
[0059] Table 3 Polarization intensity and reversal barrier of V / GY at different reaction stages
[0060]
[0061]
[0062] Example 6
[0063] Using two-dimensional gydne film as substrate, Fe atoms are adsorbed in the pores of the two-dimensional gydne film. The thickness of the two-dimensional gydne film is 100nm. The ratio of the number of Fe atoms to the number of two-dimensional gydne pores is 1:1. The ferroelectric material is recorded as Fe / GY.
[0064] Two-dimensional graphene and iron sulfate were dispersed in water in a ratio of carbon atoms to Fe atoms of 6:1. After stirring for 12 hours, the reaction solution was collected, centrifuged, washed, and freeze-dried to obtain the ferroelectric material Fe / GY.
[0065] Example 7
[0066] Using two-dimensional gydne film as substrate, Co atoms are adsorbed in the pores of the two-dimensional gydne film. The thickness of the two-dimensional gydne film is 50nm. The ratio of the number of Co atoms to the number of two-dimensional gydne pores is 0.7:1. The ferroelectric material is recorded as Co / GY.
[0067] Two-dimensional graphene and cobalt chloride were dispersed in water at a ratio of carbon atoms to Co atoms of 6:0.7. After stirring for 12 hours, the reaction solution was collected, centrifuged, washed, and freeze-dried to obtain the ferroelectric material Co / GY.
[0068] Example 8
[0069] Using two-dimensional gydne film as substrate, Ni atoms are adsorbed in the pores of the two-dimensional gydne film. The thickness of the two-dimensional gydne film is 50nm. The ratio of the number of Ni atoms to the number of two-dimensional gydne pores is 0.3:1. The ferroelectric material is recorded as Ni / GY.
[0070] Two-dimensional graphene and nickel nitrate were dispersed in water at a ratio of carbon atoms to Ni atoms of 20:1. After stirring for 12 hours, the reaction solution was collected, centrifuged, washed, and freeze-dried to obtain the ferroelectric material Ni / GY.
[0071] Example 9
[0072] With two-dimensional graphene film as substrate, Mn atoms are adsorbed in the pores of the two-dimensional graphene film. The thickness of the two-dimensional graphene film is 15 nm. The ratio of the number of Mn atoms to the number of two-dimensional graphene pores is 0.5:1, which is recorded as Mn / graphene.
[0073] Example 10
[0074] Using two-dimensional graphene oxide film as substrate, Mn atoms are adsorbed in the pores of the two-dimensional graphene oxide film. The thickness of the two-dimensional graphene oxide film is 15 nm. The ratio of the number of Mn atoms to the number of two-dimensional graphene oxide pores is 0.5:1, which is recorded as Mn / GO.
[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A ferroelectric material based on two-dimensional materials and heteroatom adsorption, characterized in that: It includes two-dimensional materials and heteroatoms. The two-dimensional material is composed of multiple layers with a porous structure. The heteroatoms are transition metal atoms. The heteroatoms are adsorbed on one side of the layer. When an electric field is applied, the heteroatoms pass through the layer through the pores to achieve positive and negative polarization switching.
2. The ferroelectric material according to claim 1, characterized in that The thickness of the two-dimensional material is 15-100 nm.
3. The ferroelectric material according to claim 1, characterized in that The transition metal atom includes at least one of a manganese atom, a chromium atom, a nickel atom, a cobalt atom and an iron atom.
4. The ferroelectric material according to claim 1, characterized in that The two-dimensional material includes at least one of graphyne, graphene, graphene oxide, doped graphene, silicene, doped silicene and transition metal sulfide.
5. The ferroelectric material according to claim 1, characterized in that The ratio of heteroatoms to two-dimensional materials is (0-1):1, excluding 0.
6. A method for preparing a ferroelectric material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The two-dimensional material and the soluble salt containing the heteroatom are dispersed in a solvent, stirred and then dried to obtain the ferroelectric material.
7. The preparation method according to claim 6, characterized in that: The soluble salt includes at least one of hydrochloride, sulfate, nitrate, acetate and a salt whose acid radical contains the heteroatom.
8. The preparation method according to claim 6, characterized in that: The stirring time is 0.1 to 24 hours, and the drying includes vacuum drying or freeze drying.
9. Use of the ferroelectric material according to any one of claims 1 to 4 in a ferroelectric memory, a non-volatile memory or a ferroelectric field effect transistor.
10. A ferroelectric memory, characterized in that: The ferroelectric material comprises the ferroelectric material as claimed in any one of claims 1 to 4.